Plans for Altering Work: Fitting Kids into Car-Management Documents in a Swedish Preschool - Thedvall, Renita (Anthropologica, 2018)
The focus of this article is Lean management action-plan documents and the type of knowledge and values they project when used in Swedish public preschools. The Lean model, also called the Toyota model, originated in the car industry. Two key features of the model were eliminating waste and ensuring that there was a system for continuous improvements in the work processes to render them as efficient as possible. The article explores the absurdities of transplanting a scientific management model and planning from the car industry to preschool, where rigid planning is not conducive to flexibility or the urgent meeting of human needs.